(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
This research seeks to know the role that accounting thinking can play in the face of financial and administrative corruption in Iraq. This traditional thinking has been criticized for its lack of dealing with corruption issues due to its flexibility and lack of application of accounting rules and standards. Financial and administrative corruption is a societal problem , Threatens all societies, especially Iraq in particular, this problem is linked to the desire of the human to obtain substantial material gains by illegal means, due to the weakness of accounting and control systems from the financial and administrative perspectives, as well as the absence of the role of accountability For accounting, financial and administrative corruption consulted in institutions and government departments such as wildfire at various levels there is no detailed joints of the state or one of its institutions except in it a bit of corruption from the failure to complete the work and the duties assigned to them, the functions of accounting and public control has lost prestige and equipped to work and achievements Achieved by the administrative organs sought by members of society. In order to achieve the objective of this research, the analytical and applied approach was used to analyze the problem of financial and administrative corruption in Iraq, and then to conclude the methods of confrontation through accounting thought, as well as to erase the bad effects of financial and administrative corruption in the Iraqi economy and the consequent renaissance and progress Comprehensive economic in Iraq.